The Influence of Problem-Based Learning Model in teacher Professional Education on Students’ Problem Solving Skills - Muhammad Hanafi; Suhartini Khalik; Usman M; Sam Hermansyah; Idayanti Idayanti; Muhammad Nawir; Sarifuddin Sarifuddin (Edumaspul: Jurnal Pendidikan, 2024)
Problem-Based Learning (PBL) has emerged as an effective pedagogical model in teacher professional education programs (Pendidikan Profesi Guru/PPG) to enhance problem-solving skills among students. This study examines the impact of PBL implementation in PPG on the development of problem-solving abilities in learners. Key findings indicate that PBL fosters critical thinking, collaborative learning, and independent study skills while promoting the practical application of theoretical concepts. Additionally, PBL encourages reflective practices and reduces students' dependency on teachers, enabling them to become self-reliant problem solvers. Recommendations for PPG include integrating simulation-based learning, emphasizing process-oriented assessments, and providing initial mentorship for novice teachers. The study concludes that PBL not only equips future educators with innovative teaching strategies but also positively influences students’ cognitive and social skills, making it a vital approach in modern education.